2023
DOI: 10.3390/healthcare11081190
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Musculoskeletal Disorders in Basketball Players: Systematic Review and Meta-Analysis

Abstract: Musculoskeletal disorders characteristically induce pain and limitations in mobility, ability, and overall functioning. In athletes, including basketball players, disorders such as back pain, postural changes, and spinal injuries are common. This systematic review aimed to evaluate the prevalence of back pain and musculoskeletal disorders in basketball players and ascertain the associated factors. Methods: The Embase, PubMed, and Scopus databases were searched for studies published in English without a time li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A longitudinal study evaluated all injuries in the National Basketball Association (NBA) players over 17 years. The study highlighted that 10.2% of all injuries involved the lumbar spine, and 0.9% were due to lumbar disk degeneration [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A longitudinal study evaluated all injuries in the National Basketball Association (NBA) players over 17 years. The study highlighted that 10.2% of all injuries involved the lumbar spine, and 0.9% were due to lumbar disk degeneration [28].…”
Section: Discussionmentioning
confidence: 96%
“…This result corresponds with the systematic review by de Carvalho Borges et al, which showed that the largest proportion of injuries occurred in the ankle (2832 injuries, 21.9%), followed by the knee (2305 injuries, 17.8%). Most authors point to the ankle as the most common site of injury; however, some authors report that the knee is the most affected region [28].…”
Section: Discussionmentioning
confidence: 99%
“…While focusing on specific areas of injury risk, these factors provide valuable insights into the state and function of the musculoskeletal system. Therefore, assessing these indicated factors and implementing appropriate preventive measures can effectively address underlying issues and reduce the risk of injury [ 15 , 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Current research unequivocally indicates that training loads can lead to structural changes in the musculoskeletal system specific to a particular sports discipline [ 16 , 19 , 20 , 21 ]. Even amateur athletes exhibit changes in the formation of anterior–posterior spinal curves [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation